CHANGES OF PRODUCTIVITY AND QUALITY PARAMETERS OF SPRING DURUM WHEAT KHARKOVSKAYA 46 UNDER INFLUENCE OF ECOLOGICAL FACTORS - M. A. Rozova; A. I. Ziborov; E. E. Egiazaryan (Труды по прикладной ботанике, генетике и селекции)
In the article the data of comparative studies of ‘Kharkovskaya 46’ecological variants which have been cultivated for a long time in Ukraine and in Altai, as well as ‘Altaika’ selected from this variety are presented. The effect of natural selection in the variety transformation at the long term cultivation under definite natural and climatic environments was demonstrated.